Observation of Bitcoin Trade for the Purpose of Hedge Trade in Global Stock Market - Raju , Valliappan; Poh Phung, Siew (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores whether Bitcoin can support and differentiate chance against the Euro STOXX, Nikkei, Shanghai A-Share, S&P 500, and the TSX Index, and looks at the elements of these capacities over various information frequencies. Pairwise GARCH models and consistent restrictive connection models are utilized for day by day, week by week, and month to month comes back from October 2010 to October 2017. We find that Bitcoin is a compelling solid fence for all these files under month to month information recurrence. In any case, day by day and week by week returns don’t exhibit solid support properties. Further recurrence reliance demonstrates tests uncover that Bitcoin returns are solid supporting against S&P and Euro records over medium information recurrence, and furthermore against the Shanghai A-Share over low information recurrence.